TRADITIONAL MARRIAGE IN THE TENGGER COMMUNITY PERSPECTIVE OF ACCULTURATION THEORY - Hakim, Abdurrahman; Naibin, Naibin; Siddiq, Syahril; Mu’allifin, M. Darin Arif; Ramadloni, Moh. Aminullah (Al-Qalam, 2024)
This research aims to analyze the acculturation of traditional marriage practices within the Tengger community, specifically investigating whether there has been a shift in customary marriage procedures following the introduction of Hinduism. To address this research question, the researcher collected data on two key traditional marriage ceremonies: Walagara and Pewawihan. In Tengger custom, these ceremonies are essential for validating a marriage. Without them, the marriage is neither recognized nor legalized according to customary law. This raises a significant inquiry on whether Walagara and Pewawihan are purely traditional customs or have been acculturated with Hindu values. The findings indicate that while Walagara and Pewawihan remain part of Tengger's heritage, their implementation has changed. Specifically, the prayers recited during these ceremonies now incorporate Hindu elements. The researcher concludes that Walagara and Pewawihan consist of two distinct components: the ritual movements, which align with Tengger custom, and the prayers, which reflect Hindu influences.